2021
DOI: 10.3390/cells10071677
|View full text |Cite
|
Sign up to set email alerts
|

Function and Biomarkers of the Blood-Brain Barrier in a Neonatal Germinal Matrix Haemorrhage Model

Abstract: Germinal matrix haemorrhage (GMH), caused by rupturing blood vessels in the germinal matrix, is a prevalent driver of preterm brain injuries and death. Our group recently developed a model simulating GMH using intrastriatal injections of collagenase in 5-day-old rats, which corresponds to the brain development of human preterm infants. This study aimed to define changes to the blood-brain barrier (BBB) and to evaluate BBB proteins as biomarkers in this GMH model. Regional BBB functions were investigated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…In this study we used a previously described preterm rat model of GMH in which near-immediate bleeding is caused by collagenase injection in the brain of P5 rat pups. 18 , 32 Saline-injected rat pups were used as controls. At 6 hours after collagenase injection, bleeding was visible on the surface of the brain, while no bleeding was observed on the brain of saline-injected control rats ( Figure 1(b) ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study we used a previously described preterm rat model of GMH in which near-immediate bleeding is caused by collagenase injection in the brain of P5 rat pups. 18 , 32 Saline-injected rat pups were used as controls. At 6 hours after collagenase injection, bleeding was visible on the surface of the brain, while no bleeding was observed on the brain of saline-injected control rats ( Figure 1(b) ).…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have reported the neuroprotective effects of Caffeine, and the antipyretic nature of NSAIDs, providing evidence that these drugs easily cross the blood–brain barrier. While blood–brain barrier permeability, as well as the maturation of neuronal cells, tight junctions, and neurochemicals, may play a key role, studies show that exposure to hypoxia causes significant vascular dysfunction and brain injury (Andersson et al, 2021). It is likely that differences in maturation and IH exposure equally contributed to the responses noted in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The resistance between transwell donor chamber and recipient chamber was measured by using a resistance meter. When the resistance value exceeded 200 Ω/cm 2 , the in vitro BBB model was regarded to be successful established [ 45 ].…”
Section: Methodsmentioning
confidence: 99%